MACROECONOMIC INDICATORS AND FOREIGN DIRECT INVESTMENT IN INDONESIA - Fitriyah, Fitriyah; Rahmawati, Farida; Narmaditya, Bagus Shandy (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2021)
ABSTRACTIndonesia has abundant diversity of resources to promote economic growth, and insufficient capital will lead to economic stagnation. This paper aims at examining the impact of macroeconomic indicators such as gross domestic product and inflation toward foreign direct investment in Indonesia as well as investigating the ease of doing business factors in explaining foreign direct investment. This research involved a time-series from 2014 to 2019, which was collected from several official websites of Statistics Indonesia (BPS), Central Bank of Indonesia (BI), the Investment Coordinating Board (BKPM), and World Bank. Furthermore, the data were analyzed undergoing multiple linear regression analyses with the Ordinary Least Square (OLS) model. The findings indicate that gross domestic product has a positive impact on foreign direct investment, while inflation has a negative effect. Also, the ease of doing business variables failed in explaining a significant influence between foreign direct investment in Indonesia.ABSTRAKIndonesia memiliki keanekaragaman sumber daya yang melimpah untuk mendorong pertumbuhan ekonomi namun permasalahan permodalan menyebabkan kelambanan yang menyebabkan stagnasi ekonomi. Penelitian ini bertujuan untuk menguji pengaruh indikator makroekonomi seperti produk domestik bruto dan inflasi terhadap investasi asing langsung di Indonesia. Penelitian ini juga menyelidiki faktor-faktor kemudahan berbisnis dalam menjelaskan investasi asing langsung. Data penelitian ini adalah time-series 2014-2019, yang diperoleh dari beberapa situs resmi termasuk Badan Pusat Statistik (BPS), Bank Sentral Indonesia (BI), Badan Koordinasi Penanaman Modal (BKPM), dan Bank Dunia. Selanjutnya data tersebut dianalisis dengan menggunakan analisis regresi linier berganda dengan model Ordinary Least Square (OLS). Hasil penelitian menunjukkan bahwa produk domestik bruto berpengaruh positif terhadap investasi asing langsung, sedangkan inflasi berpengaruh negatif. Selain itu, variabel kemudahan berbisnis gagal menjelaskan pengaruh yang signifikan antara investasi asing langsung di Indonesia.